1027 DEVELOPING A MINIMUM COMMON DATASET FOR HIP FRACTURE AUDIT. (14th June 2022) - Poacher, A; Ojeda-Thies, C; Hall, A; Ahern, E; Brent, L; Costa, M; Johansen, A
Abstract: Introduction: National hip fracture audits share a common heritage in the work of Rikshöft and the Standardised Audit of Hip Fracture in Europe. However, as more countries develop audit programmes and these evolve to address local needs, divergence in the data they collect compromises their scope for learning from clinical, audit and quality improvement work in other nations. Method: In 2021 we compared all ten established national hip fracture audits: England/Wales/Northern Ireland; Scotland; Australia/New Zealand; Ireland; Germany; the Netherlands; Sweden; Norway; Denmark; Spain. We tabulated all questions included in each, and cross-referenced them against the 32 questions of the minimum common dataset (MCD) defined by the global Fragility Fracture Network (FFN) in 2014. We identified those consistently used in most national audits, and additional fields that might need to form part of a revised MCD. Any MCD must meet the needs of both developed and developing countries. We presented these findings at the Asia-Pacific FFN meeting, and used an online questionnaire to capture feedback from different countries. A draft revision was presented at the Global FFN conference in September 2021, with feedback again used to finalise this revised MCD. Results: We tabulated a total of 215 possible questions. Only 72 (34%) were used in >1 national audit, and only 32 (15%) by more than half of audits. Adherence to the 2014 MCD was disappointing; all 32 fields were used by at least one audit, but 5/32 only by one audit. Only 21/32 (65%) were used in the majority, and only three (anaesthetic grade, operation and date/time of surgery) by all ten established audits. Discussion: This revised MCD will help aspirant nations establish new audit programmes, facilitate the integration of novel analytic techniques and greater multinational collaboration, and serve as an internationally-accepted standard for monitoring and improving hip fracture services.